Outer Membrane Vesicles (OMVs) of Gram-negative Bacteria: A Perspective Update - Jan, Arif Tasleem (Frontiers in Microbiology, 2017)
Outer Membrane Vesicles (OMVs; synonymous to exosomes) of Gram-negative bacteria are spherical membrane-enclosed entities of endocytic origin. Reported in the consortia of different bacterial species, production of OMVs into extracellular milieu seems essential for their survival. Enriched with bioactive proteins, toxins, and virulence factors, OMVs play a critical role in the bacteria-bacteria and bacteria-host interactions. Emerged as distinct cellular entities, OMVs help bacteria in adaptation to diverse niches, in competing with other bacteria to protect members of producer species and more importantly on the forefront of host-pathogen interaction. The utility of the composition of OMV, their capability of modulating host immune response along with coordinated secretion of bacterial effectors attributes them with weaponry to withstand diverse environments. Study of the OMV production under natural and diverse stress conditions are believed to broaden the horizons and open up new frontiers of delineating the molecular machinery of disease pathogenesis. Playing diverse biological and pathophysiological functions, OMVs hold a great promise in the context of the resurgence of bacterial diseases with a steep decline in the efficiency of antibiotics. Having multifaceted role, their emergence as a causative agent for a series of infectious diseases increases the probability of their exploitation in the development of effective diagnostic tools and as vaccines against diverse pathogenic species of Gram-negative origin.